Evaluating Pedestrian Level of Service at Signalized Intersections in China: Intercept Survey Method. Issue 1 (January 2015) - Ling, Ziwen; Cherry, Christopher R.; Ni, Ying; Li, Keping
Approximately 1.24 million people die annually in road traffic deaths around the world, and more than 90% of those deaths occur in low-income and middle-income countries, such as China. Pedestrians are the most vulnerable components of road traffic; therefore, it is important to develop more refined methods of improving their walking experience. With use of an intercept survey (IS) method, the influence of pedestrians' characteristics, traffic design, and operation factors on pedestrian level of service (LOS) was evaluated. Factors related to pedestrians' perception and traffic operation had significant impacts on pedestrian LOS. When possible effects of other variables were held constant, significant factors included age, travel purpose, single-step crossing, nearside crossing, and conflicts with left-turning vehicles. Perceived and actual waiting times were compared, and when actual waiting time exceeded 60 s, the perceived waiting time increased faster than the actual waiting time. At 120 s, perceived waiting time was 50% longer than was actual waiting time. An ordered logit model of pedestrian LOS was constructed to evaluate pedestrian LOS in China. This study found several factors more influential in and specific to China than did other international LOS studies. The IS approach was compared with other LOS methods that are part of a series of studies of pedestrian LOS in China. Suggestions are provided on the applicability of IS, contingent field survey, and pedestrian crossing video simulation methods. IS was found to be more suitable for crosswalks of moderate to high levels of pedestrian LOS. Pedestrian crossing video simulation is not recommended for crosswalks with a high possibility of red light crossing.